Health literacy and factors associated with breast self-examination behavior among at-risk women in Khao Rup Chang Subdistrict, Mueang Songkhla District, Songkhla Province - Teanuan, Yaowalak; Rattanakornpreeda, Patchanok (Journal of Medical and Public Health Region 4, 2026)
Breast cancer is a major public health concern and a primary cause of mortality among women globally. Early detection through breast self-examination (BSE) is a crucial strategy. This cross-sectional analytical study aimed to investigate the level of breast cancer health literacy and its association with breast self-examination behavior among 400 at-risk women in Khao Rup Chang Subdistrict, Mueang Songkhla District, Songkhla Province. The data collected were analyzed using a validated questionnaire and analyzed with descriptive statistics and Spearman’s Rank Correlation Coefficient. The results showed that most women had a moderate level of breast cancer health literacy ( = 3.52, SD = 0.78), but 60% showed inadequate knowledge about BSE. Despite having a positive attitude towards BSE (84.25%), only 57.5% of participants engaged in regular BSE behavior and only 29.50% performed the correct technique. Social support had the strongest positive correlation with BSE behavior (rs = 0.79, p < 0.01), followed by health literacy (rs = 0.66, p < 0.01). Knowledge and attitude also had a weak positive correlation with BSE behavior (rs = 0.37, rs = 0.22, p < 0.01). The findings suggest that continuous efforts should be made to improve health literacy and practical skills through demonstrations and hands-on training, along with strengthening community-based social support, to enhance the long-term effectiveness of BSE and promote early breast cancer detection.